Princípios do merecimento de pena e da necessidade de pena como fundamento da punibilidade e seus reflexos na interpretação e a aplicação do art. 59 do Código Penal - Cunha, Tiago Lorenzini (2016)
This thesis aims to deepen the criminal legal study on the principles of merit and worth of the need for punishment as the basis for criminal liability and its impact on the interpretation and application of art. 59 of the Brazilian Penal Code. Thus, the literature review method is used, in order to achieve the hypothesis that the legal and penal principles of the worthiness and the need for punishment, as the basis of punishing, are inserted as criteria for interpretation and systematization of criminal and analysis of the types practiced unfair - for the legislator and the magistrate respectively. For this reason, the considerations - especially - criminal policy would be beyond the culpable unfair, that is, they could not be supported by the typicality, the unlawfulness and the culpability (classical theory of the crime). In this way, the effects of criminality and its principles for the interpretation and application of art. 59 PC, above all, are approached as well as an epistemological limit to the power of judicial discretion. This is because there is no unanimity currently in the doctrine of the scope of the material meaning and of the function of the penalty merit and / or need to punishment in the current state of criminal dogmatic. These concepts, widely studied by the German doctrine - ("Strafwürdigkeit" and "Strafbedürftigkeit" respectively) - and which are used not only as the basis for a rapprochement between the Criminal Law and Criminal Policy. They also boost numerous efforts in other expressions of our doctrine, particularly in a teleological orientation and systematic criminal legal dogmatic, they would also be assumptions of criminality category - or, for some, dissolved in or out of the offense structure. In this sense, the importance of discussing the legitimizing core of the objective conditions of criminality, of absolving excuses and other causes that exempt or prevent the imposition of a penalty; as well as the proposal of stringency or flexibility of crime theory in a new concept (material) of crime.